Nurses’ Knowledge of the Model of Care in the Eastern Health Cluster of Saudi Arabia: A Cross-Sectional Study - Amal Suliman Al Suliman; Myra Cusi Britiller; Latha S Kannan; Nahla Shehabelden; Zainab Al Swaid; Maryam AlKhalaf; Eman M Gaber Hassan (Fundamental and Management Nursing Journal, 2026)
Introduction: Aligned with Saudi Vision 2030, the Ministry of Health initiated a comprehensive restructuring plan to enhance the quality and efficiency of healthcare delivery. A central component of this transformation is the establishment of health clusters across the Kingdom and the implementation of the new Model of Care (MoC), which emphasizes preventive health and integrated service delivery. However, the successful implementation of the MoC largely depends on healthcare professionals’ understanding and application of its principles. This study aimed to assess nurses’ knowledge of the MoC within the Eastern Health Cluster of Saudi Arabia. Methods: A descriptive, cross-sectional design was utilized, involving 217 nurses. Data were collected using a validated, MoC-based survey distributed electronically via Google Forms through various social media platforms. Descriptive statistics summarized nurses' MoC knowledge and demographic information. The Shapiro-Wilk test and Kruskal-Wallis test were used to examine differences between groups. Results: Findings indicated a mean knowledge score of 8.52 (SD = 2.44) with a median of 9. There were no statistically significant differences in knowledge scores based on gender (U(215) = 735, p = 0.561), nationality (U(215) = 5271, p = 0.481), nurses’ functions (χ²(4) = 8.43, p = 0.077), or years of experience (χ²(4) = 1.66, p = 0.798). Conclusions: Although nurses show general awareness of the MoC, their familiarity remains basic. The findings emphasize the importance of structured education and ongoing in-service training to support MoC implementation and contribute to realizing Saudi Vision 2030 goals.